DISAIN MATERI PENDIDIKAN AGAMA ISLAM DI PESANTREN MODERN AL IKHLAS KUNINGAN JAWA BARAT (STUDI KASUS DISAIN MODEL BELAJAR EDUTAINMENT PENDEKATAN SOMATIK, AUDITORY, VISUAL DAN INTELEKTUAL) - Ike Nilawati Rohaenah; Sahudi; Nur Wadjah Ahmad; Andewi Suhartini (FAKULTAS TARBIYAH IAI SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2021)
The research method used is a mini research field research (field research) is qualitative descriptive. Data obtained by means of observation, interviews, and documentation. Data were analyzed, starting from data reduction, data presentation, drawing conclusions and testing the validity of the data through triangulation. The purpose of this study is to identify and analyze the material design of Islamic religious education in the modern Islamic boarding school Al Ikhlas Kuningan, West Java. Somatic, Auditory, Visual and Intellectual Approaches Edutainment. The results show that students are happy to take part in Islamic Religious Education (PAI) learning activities using the Edutainment learning model with Somatic, Auditory, Visual and Intellectual approaches. Student findings are easy to understand/understand and enjoyable Islamic Religious Education PAI through Edutainment learning model approaches Somatic, Auditory, Visual and Intellectual.